2010
DOI: 10.1007/s10681-010-0271-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis, molecular diversity, combining ability and their interrelationships in short duration maize (Zea mays L.) across the environments

Abstract: Five inbred lines, 10 single cross maize (Zea mays L.) hybrids and two standard cultivars as check were used to study the combining abilities and heterosis under three environmental conditions. Random amplified polymorphic DNAs (RAPDs) markers were used to study the genetic diversity (GD) and further to analyze relationship of RAPDs based GD with combining ability and heterosis in short duration maize. Spearman's rank correlation coefficients and linear regressions were analyzed to identify the most important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 30 publications
6
22
0
Order By: Relevance
“…GD mor had highly significant positive correlation with plant height of maize par-ents and reciprocal hybrids with values 0.968 and 0.908, respectively. These results corroborate with previous studies (Lee et al, 2007;Devi and Singh, 2011). The ability to predict heterosis levels using genetic distance between the parents varied for the different traits.…”
Section: Mean Performance Of Teosinte Maize and Their Hybridssupporting
confidence: 92%
See 1 more Smart Citation
“…GD mor had highly significant positive correlation with plant height of maize par-ents and reciprocal hybrids with values 0.968 and 0.908, respectively. These results corroborate with previous studies (Lee et al, 2007;Devi and Singh, 2011). The ability to predict heterosis levels using genetic distance between the parents varied for the different traits.…”
Section: Mean Performance Of Teosinte Maize and Their Hybridssupporting
confidence: 92%
“…The relationship between molecular marker distance and heterosis remains unclear. Some of the reports state significant association (Lanza et al, 1997;Amorim et al, 2006;Srdic et al, 2007) whereas, the others state non-significant or no association between markers based GD and heterosis (Shieh and Thseng, 2002;Legesse et al, 2008;Devi and Singh, 2011).…”
mentioning
confidence: 99%
“…Betrán et al (2003) reported a highly significant correlation between GD and SCA effects (r = 0.8) in maize under stress and non-stress conditions. Devi and Singh (2011) demonstrated that SCA could emerge as an important factor in the determination of heterosis and per se performance of the hybrids. However, Ceballos et al (2016) observed weak associations between the GD and SCA effects, which presented r 2 values ranging from 0.00 to 0.28.…”
Section: Introductionmentioning
confidence: 99%
“…Inbred parents performance, combining ability and genetic diversity among them are considered to be important factors determining success of single cross hybrid development programme (Devi and Singh, 2011). Due to involvement of only two parents, the adaptability of single cross hybrids to the existing environmental conditions due to global climate change has been questioned.…”
Section: Introductionmentioning
confidence: 99%